Alterations in Peripheral B Cell Subsets Correlate with the Disease Severity of Human Glaucoma - Yu L; Chen Y; Xu X; Dong Q; Xiu W; Chen Q; Wang J; He C; Ye J; Lu F (Dove Medical Press, 2021)
Ling Yu,1,* Yang Chen,2,* Xiang Xu,2 Qiwei Dong,2,3 Wenbo Xiu,2 Qinyuan Chen,2 Jinxia Wang,2 Chong He,2,3 Jian Ye,1 Fang Lu2,3 1Department of Ophthalmology, Daping Hospital, Army Medical Center, Army Medical University, Chongqing, People's Republic of China; 2Clinical Immunology Translational Medicine Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 3Medico-Engineering Cooperation on Applied Medicine Research Center, University of Electronic Science and Technology of China, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Fang LuClinical Immunology Translational Medicine Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, 32 The First Ring Road West 2, Chengdu, Sichuan, 610072, People's Republic of ChinaTel/Fax +86-028-87394201Email lufangfang@126.comJian YeDepartment of Ophthalmology, Daping Hospital, Army Medical Center, Army Medical University, No. 10, Changjiang Branch, Daping, Yuzhong District, Chongqing, 400042, People's Republic of ChinaTel/Fax +86-023-68811229Email yejian1979@163.comBackground: Glaucoma is a group of retinal neurodegenerative diseases causing irreversible visual impairment. The pathogenesis of this disease is complicated. Studies have shown that the immune system is involved in the neurodegenerative process of glaucoma. There are continuous evidences that autoantibodies play a crucial role in the pathogenesis of glaucoma. However, focuses on B cells, the antibody-producing cells in glaucoma are surprisingly limited.Methods: Fresh peripheral blood samples were collected from 44 glaucoma patients (38 with primary angle-closure glaucoma (PACG) and 6 with (primary open-angle glaucoma POAG)) and 36 age-matched healthy donors (HD). Density gradient centrifugation was performed to obtain peripheral blood mononuclear cells (PBMC). Flow cytometry was performed to determine B cell phenotypes. The severity of glaucoma was determined based on the mean deviation (MD) of visual field.Results: In this study, we demonstrated that total B cells was significantly increased in glaucoma patients compared to HD. Next, we checked changes of different B cell subsets in glaucoma. Glaucoma patients were found to have a significant increase in the frequencies of antibody-secreting cells (ASC)/plasmablasts, naïve, and CD19+ CD27− IgD− double negative (DN) subpopulations, but a decrease in the CD27+ IgD+ unswitched memory compartment. Notably, we found that the increment of CD27− IgD− DN B cells was significantly magnified according to the clinical severity.Conclusion: We demonstrate, for the first time, that peripheral B cell subsets are altered and unveil the correlation of a newly identified pro-inflammatory CD27− IgD− DN subset with clinical features of glaucoma, suggesting that these B cell subsets could serve as potential biomarkers to monitor the disease progression of glaucoma patients.Keywords: glaucoma, B cells, CD27− IgD− double negative B cells, retinal neurodegeneration